AKUISISI BUKTI DIGITAL PADA APLIKASI TAMTAM MESSENGER MENGGUNAKAN METODE NATIONAL INSTITUTE OF JUSTICE - Mualfah, Desti; Viransa, Afdel; Amran, Hasanatul Fu’adah (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
Smartphones are one of the tools used in carrying out daily work activities, the number of active social media users in Indonesia in January 2019 reached 150 million, 130 million of whom accessed social media using smartphones. With the development of smartphones in social media, many are misused using instant messaging applications, one of which is cybercrime such as cyberbullying, human trafficking systems, fraud and so on. Cyberbullying is one of the negative impacts in cyber crime through the use of applications that are often used, namely the TamTam Messenger social media. The problem that will be discussed in this study is the digital forensic process, especially mobile forensics in order to find digital evidence that was deleted on the TamTam Messenger application using the MobileEdit forensic tools and the National Institute of Justice method. The results of this study show that using the MobileEdit forensic tools and the National Institute of Justice method succeeded in recovering digital evidence that had been deleted by the perpetrator on the TamTam Messenger application.